Protein Kinase D2 drives chylomicron‐mediated lipid transport in the intestine and promotes obesity - Jonathan Trujillo‐Viera; Rabih El‐Merahbi; Vanessa Schmidt; Till Karwen; Angel Loza‐Valdes; Akim Strohmeyer; Saskia Reuter; Minhee Noh; Magdalena Wit; Izabela Hawro; Sabine Mocek; Christina Fey; et al. (EMBO Molecular Medicine, 2021)
Abstract Lipids are the most energy‐dense components of the diet, and their overconsumption promotes obesity and diabetes. Dietary fat content has been linked to the lipid processing activity by the intestine and its overall capacity to absorb triglycerides (TG). However, the signaling cascades driving intestinal lipid absorption in response to elevated dietary fat are largely unknown. Here, we describe an unexpected role of the protein kinase D2 (PKD2) in lipid homeostasis. We demonstrate that PKD2 activity promotes chylomicron‐mediated TG transfer in enterocytes. PKD2 increases chylomicron size to enhance the TG secretion on the basolateral side of the mouse and human enterocytes, which is associated with decreased abundance of APOA4. PKD2 activation in intestine also correlates positively with circulating TG in obese human patients. Importantly, deletion, inactivation, or inhibition of PKD2 ameliorates high‐fat diet‐induced obesity and diabetes and improves gut microbiota profile in mice. Taken together, our findings suggest that PKD2 represents a key signaling node promoting dietary fat absorption and may serve as an attractive target for the treatment of obesity.